Bodies in Protest : Hunger Strikes and Angry Music - Simeant, Johanna; Träini, Christophe (Book collections on Project MUSE., 2016)
Research on social movements has historically focused on the traditional weapons of the working class, especially labor strikes and street demonstrations-but everyday actions, such as eating or singing, which can also be turned into a means of protest, have yet to be fully explored. Originally published as La greve de la faim by Johanna Simeant and La musique en colere by Christophe Traïni, Bodies in Protest is an interdisciplinary and comparative history of these modes of action that reveals how hunger strikes and music ranging from gospel songs to rock anthems can efficiently convey political messages and mobilize the masses. Common to both approaches, the chapters show, is a direct appeal to the emotions and a reliance on the physical, concrete language of the human body.